A dye-loaded nonlinear metal-organic framework as self-calibrated optical thermometer. (June 2022) - Wan, Yating; Yu, Libing; Xia, Tifeng
Abstract: Facile and accurate temperature measurement is crucial in daily life, industrial applications, and scientific research. Here, we present a new strategy for physiological temperature sensing based on dual-emission from second harmonic generation (SHG) signal and two-photon luminescence in a dye-loaded nonlinear metal-organic framework (MOF) composite FIR-8⊃DMASM (DMASM = 4-[p-(dimethylamino)styryl]-1-methylpyridinium). Powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), infrared absorption spectrum, single-photon luminescence, and the quantum yield indicate that encapsulation not only provides a two-photon luminescence center, but also improves the stability and quantum efficiency of dyes. Temperature-dependent spectroscopy shows that FIR-8⊃DMASM has excellent sensory performance in the physiological temperature region (20–60 °C) with high relative sensitivity of 1.36–2.98% o C −1 . With good water stability and excellent biocompatibility, FIR-8⊃DMASM can be potentially applied in biological temperature sensing. Graphical abstract: A dye-loaded metal-organic framework FIR-8⊃DMASM shows excellent self-calibrated physiological temperature sensing performance with high relative sensitivity of 1.36–2.98% o C −1, good water stability, and excellent biocompatibility. Image 1 Highlights: Physiological thermometer based on dual-emitting MOF⊃dye composite has been realized. Two signals for sensing are SHG and two-photon luminescence in MOF⊃dye composite. FIR-8⊃DMASM exhibits high relative sensitivity, good repeatability, water stability and biocompatibility.